2016
DOI: 10.1016/j.matdes.2016.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of La intermetallics on the structure and tensile properties of thin section gravity die-cast A357 Al alloy

Abstract: In current research different amounts of La (0.01, 0.03, 0.05, 0.07, 0.1, 0.3, 0.5 and 1 wt%) were added to A357 aluminum alloy to investigate the structure and tensile properties of thin section parts prepared by gravity die-casting. The cast specimens were examined by using optical microscopy (OM), scanning electron microscopy (SEM), tensile testing and determination of quality index values to evaluate the modification efficiency of the alloy by La addition. Obtained results revealed that La reduces the grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…If the amount of rare earth added to the alloy exceeds a certain value, the rare earth element will be enriched at the front of the solidification interface (it is shown in Figure 5) and prevent the diffusion of other alloying elements into the solid phase, then reduce the solid solubility of alloy elements in matrix α-Al, make the number of eutectic increase, cause segregation and reunion, hinder the refinement effect, and make the organization begin to deteriorate. Furthermore, Pourbahari [32] reported that, at a higher La levels, the new La-rich intermetallic (AlSiLa intermetallic) slows the growth rate of the α-Al primary phase. It reduced the strengthening phase of the alloy.…”
Section: Microstructure and Microhardnessmentioning
confidence: 99%
“…If the amount of rare earth added to the alloy exceeds a certain value, the rare earth element will be enriched at the front of the solidification interface (it is shown in Figure 5) and prevent the diffusion of other alloying elements into the solid phase, then reduce the solid solubility of alloy elements in matrix α-Al, make the number of eutectic increase, cause segregation and reunion, hinder the refinement effect, and make the organization begin to deteriorate. Furthermore, Pourbahari [32] reported that, at a higher La levels, the new La-rich intermetallic (AlSiLa intermetallic) slows the growth rate of the α-Al primary phase. It reduced the strengthening phase of the alloy.…”
Section: Microstructure and Microhardnessmentioning
confidence: 99%
“…Continue increasing solution time to 3 h (Figure c), more Sr element diffuse into α ‐Al and the distribution is more homogeneous. As for La element, it distributes uniformly and changes little under all of the conditions, because La and La‐containing phases are considered as the nucleation cores of α ‐Al . In addition, as a type of surface active agent, La can promotes the diffusion of Mg and Si in the matrix, and decreases conglomeration of impurities in unit area and grain boundaries .…”
Section: Discussionmentioning
confidence: 99%
“…The other elements provided only a minor refinement of the plate-like silicon morphology. Pourbahari et al [12] studied the effects of La addition and heat treatment on the microstructure and tensile properties of A357 aluminum alloy. Their results showed that the addition of La obviously reduced the size and area of eutectic silicon particles after heat treatment.…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%